Ethical Aspects of Software Engineering:A wake up call for India - Iqbal, Juneed; Maqbool Beigh, Bilal (International Journal of Computer Sciences and Engineering, 2025)
Software Engineering has a direct and vigorous effect on individuals, societies, nations and to the whole world. Ignoring or not considering social context of software development can lead to catastrophic consequences. India which has become global leader as its software industry is touching skies can’t sustain it unless its software engineers do not practise better Software design and development practices. Indian government is pushing its software industry further up by its digital India program, creating an ecosystem full of technical manpower, elite technical institutes etc. With the tremendous growth of software development in India, there are also serious threats due to lack of ethics and professionalism.